Mortality rates and life expectancy improvements among malaysian elderlies - Nur Shatikah Mohamad Ibrahim; Syazreen Niza Shair; Aida Yuzi Yusof (Institute of Advanced Engineering and Science, 2020)
This paper presents a study on mortality rates and life expectancy improvements among elderly people in Malaysia. The central age-specific mortality rates will be analyzed according to genders. The expectation of future lifetime of these old age people will be estimated using the actuarial life table approach. Two different types of life table will be developed, including life table for males and females— to compare the results of mortality rates and life expectancies between genders. Results show that, mortality rates of Malaysian elderly, for both males and females are increasing almost in linear pattern by age, and this trend is consistent from 1950 to 2015. Comparison between genders shows that mortality of elderly females is generally lower than males at almost all ages. Nonetheless, mortality rates of Malaysian elderly males are declining faster than Malaysian elderly females. Life expentancies of females are higher than males for age groups 60 to 70, and lower than males for age 75 and above. Results also indicate that Malaysian elderly popultion is aging faster from previous generation in which elderly males age 85+ in 2010-2015 can live longer by 123% than thise in 1950-1955.